People’s Perceptions on Forest Management Sustainability in Far-Western Nepal - Pant, Keshab Raj (Banko Janakari, 2025)
Public perception of community forests (CFs) is crucial for their sustainability and for addressing future challenges in forest resource management. This study, based on descriptive and explanatory field research, examines community roles in forest management, perceptions of sustainability, and key challenges facing community forest management over the next decade. Taking into account diverse socioeconomic and geographic contexts, surveys were conducted with 368 households from 19 Community Forest User Groups (CFUGs) across four districts. The findings indicate strong community support for the community forest model but reveal significant gender disparities in management roles, with men more likely to see themselves as managers and women as users. Statistical tests confirm these gender differences in community forest management roles. While most respondents perceive their forests as sustainable, invasive species, forest fires, climate change, governance issues, and resource-sharing conflicts remain major threats for the coming decade. Addressing these challenges requires urgent management attention and the development of comprehensive resource management plans to ensure the long-term sustainability of forest management.